Bibliometric Analysis of Turkey’s Research Activity in the Anatomy and Morphology Category from the Web of Science Database - Bahşi, İlhan and Adanır, Saliha Seda and Kervancıoğlu, Piraye and Orhan, Mustafa and Govsa, Figen (European Journal of Therapeutics, 2021)
Objective: The measurement of international publication activities is one of the essential indicators used to evaluate the scientific development level of countries. Although many studies are using the bibliometric method in the literature, it is seen that there are very few bibliometric studies in the field of anatomy. This study aimed to analyze the articles bibliometrically which conducted by researchers at institutions from Turkey and indexed in Science Citation Index Expanded (SCI-E) of the Web of Science database in the category of Anatomy and Morphology. Materials and Methods: According to 2019 data, journals in the Anatomy and Morphology category and indexed in the SCI-E were determined. Publications from Turkey that were published in these journals was determined. The full-texts of these articles were examined, and study types were defined. Also, VOSviewer software was used to create a collaboration and word co-occurrence network. Results: It was determined that there were 48,002 publications in 21 journals. It was found that 1,461 publications (3.04%) have at least one author from Turkey. The total number of citations was 11,728 for these publications. The average number of citations was 8.02±11.95. The radiological studies have increased statistically more than both experimental animal and cadaveric studies by years. In addition, it has been determined that the total number of articles, especially the radiological studies, has increased significantly over the years. Conclusion: The increase in the number of scientific studies in the field of anatomy is important in terms of the contribution of Turkey to literature in this area.